Long Term Rescue of the TSH Receptor Knock-Out Mouse – Thyroid Stem Cell Transplantation Restores Thyroid Function - Latif, Rauf; Ma, Risheng; Morshed, Syed A.; Tokat, Bengu; Davies, Terry F. (Frontiers in Endocrinology, 2021)
The synergistic activation of the transcription factors can lead to thyroid progenitor cell speciation. We have previously shown in vitro that mouse or human stem cells, expressing the transcription factors NKx2-1 and Pax8, can differentiate into thyroid neo-follicular structures (TFS) . We now show that syngeneic mouse TFS when implanted into hypothyroid TSH receptor knockout (TSHR-KO) mice can ameliorate the hypothyroid state for an extended period. ES cells derived from heterozygous TSHR-KO blastocysts were stably transfected with Nkx2-1-GFP and Pax8-mcherry constructs and purified into 91.8% double positive cells by flow cytometry. After 5 days of activin A treatment these double positive cells were then induced to differentiate into neo-follicles in Matrigel for 21 days in the presence of 500μU/mL of TSH. Differentiated thyroid follicle structures expressing thyroglobulin mRNA were implanted under the kidney capsule of 4-6 weeks old TSHR-KO mice (n=5) as well as hind limb muscle (n=2) and anterior chamber of one eye (n=2). Five mice tested after 4 weeks were all rendered euthyroid and all mice remained euthyroid at 20 weeks post implantation. The serum T4 fully recovered (pre-bleed 0.62±0.03 to 8.40±0.57 µg/dL) and the previously elevated TSH became normal or suppressed (pre-bleed 391±7.6 to 4.34±1.25 ng/dL) at the end of the 20 week observation period. The final histology obtained from the implanted kidney tissues showed only rudimentary thyroid follicular structures but which stained positive for thyroglobulin expression. The presence of only rudimentary structures at the site of implant on these extended animals suggested possible migration of cells from the site of implant or an inability of TFCs to maintain proper follicular morphology in these external sites for extended periods. However, there were no signs of tumor formation and no immune infiltration. These preliminary studies show that TSHR-KO mice are a useful model for orthotropic implantation of functional thyroid cells without the need for thyroidectomy, radioiodine ablation or anti thyroid drug control of thyroid function. This approach is also proof of principle that thyroid cells derived from mouse ES cells are capable of surviving as functional neo-follicles in vivo for an extended period of 20 weeks.